Method for carrying out electrochemical synthesis reaction by taking inorganic solid electrolyte as diaphragm

Through the inorganic solid electrolyte membrane, the problems of easy damage and high cost in the existing electrochemical synthesis technology are solved, and efficient and stable electrochemical reactions are achieved. They are suitable for a variety of reaction types and reduce equipment operation costs.

CN119177472AActive Publication Date: 2024-12-24SUZHOU UNIV
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411681647.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2024-12-24
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

In the existing electrochemical synthesis technology, the electrolyte separator is prone to damage under high voltage, high current and organic solvent environments, resulting in high equipment cost, short service life, and difficult to adapt to various reaction types, limiting the large-scale application of electrolytic devices.

Method used

The multi-porous electrolyte membrane with garnet-type, fluorite-type oxide or perovskite structure is prepared by sol-gel method, gel injection molding method, electrospinning method and other methods. Electrochemical synthesis reaction to achieve efficient isolation and highly selective redox reaction.

Benefits of technology

Inorganic solid electrolyte membrane has good chemical stability, long service life and low cost. It is suitable for a variety of electrochemical reactions, including electrolytic water, synthetic ammonia and organic compounds synthesis, improving system efficiency and safety and reducing operating costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177472A_ABST
    Figure CN119177472A_ABST
Patent Text Reader

Abstract

The invention provides a method for carrying out electrochemical synthesis reaction by taking inorganic solid electrolyte as a diaphragm. The method comprises preparation of the inorganic solid electrolyte and a method for carrying out electrochemical synthesis reaction by taking the inorganic solid electrolyte as the diaphragm. The inorganic solid electrolyte is of a layered structure or a uniform distribution structure formed by one or more of garnet type electrolyte, fluorite type oxide electrolyte, perovskite structure oxide electrolyte and LAMOX series electrolyte, has a controllable microporous structure, resists strong acid, strong alkali and various organic solvents, can block penetration of reaction molecules, and can be used for preparing the electrolyte. The anode chamber and the cathode chamber are simultaneously subjected to high-efficiency and high-selectivity oxidation and reduction reaction; the method is reasonable in design, convenient to operate and low in cost, and is generally suitable for important synthesis reactions such as water electrolysis, electrochemical oxidation, hydrogenation, halogenation, ammonification and coupling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an inorganic solid electrolyte and a method for performing an electrochemical synthesis reaction using the inorganic solid electrolyte as a diaphragm. The method comprises the preparation of the inorganic solid electrolyte and a method for performing an electrochemical synthesis reaction using the inorganic solid electrolyte as a diaphragm. The method belongs to the fields of material synthesis, electrochemical energy conversion and electrosynthetic chemistry. Background Art

[0002] Electrochemistry is a clean and sustainable synthesis technology. It is the core of realizing large-scale production of green hydrogen, precise synthesis of high-value-added fine chemicals, efficient utilization of carbon dioxide, and low-energy synthesis of ammonia (Science 2020, 368,1181-1182; JACS Au 2022, 2, 5, 1054-1070; ACS Catal. 2024, 14, 8, 6045-6061;Acc. Chem. Res. 2020, 53, 3, 545-546). In the electrochemical process, reduction and oxidation reactions occur in the cathode chamber and the anode chamber respectively. The electrolyte membrane can conduct electricity through ion transport, separate the two chambers to isolate the diffusion and migration of reduction products and oxidation products between the two chambers, and is an indispensable core component to ensure the safe, stable and efficient operation of the electrochemical system.

[0003] Taking water electrolysis as an example, the current mainstream water electrolysis hydrogen production technologies include alkaline water electrolysis (AWE), anion exchange membrane water electrolysis (AEM) and proton exchange membrane water electrolysis (PEM) (Energy Environ. Sci. 2023, 16, 1384-1430). AWE technology has become the most widely used method due to its maturity and economy. However, in actual engineering applications, AWE technology faces challenges such as low current density, slow dynamic response, membrane cross-gassing and corrosion equipment. In order to overcome these problems, researchers developed AEM technology (Chem. Rev. 2024, 124, 10, 6393-6443). AEM technology uses a low-cost anion exchange membrane as a diaphragm and uses pure water or weak alkaline solution as an electrolyte to slow down equipment corrosion, showing good air tightness, stability and low resistivity, but its limitations are low ionic conductivity and insufficient high-temperature stability. PEM technology uses proton exchange membrane as a diaphragm and is known for its high current density and fast responsiveness, but its cost is as high as 3,000 yuan / kilowatt, and voltage fluctuations during operation will lead to reduced electrolysis efficiency (Curr. Opin. Green Sustain. 2024,47: 100932).

[0004] Electrolyte membranes also play a key role in the electrochemical synthesis of fine chemicals. Most of the electrochemical synthesis reactions reported in the literature at room temperature and liquid phase conditions have selected membranes that are selectively permeable to ions, such as proton exchange membranes and bipolar membranes (Science 2020, 368, 1228–1233; Nat. Commun. 2022, 13,3125; Adv. Funct. Mater. 2019, 29, 1904780). However, existing membranes are not tolerant to organic solvents and solutions containing some special ions (such as halogen ions). Long-term contact with them will cause the membrane to dissolve, limiting the type of organic synthesis reactions. Damage to the membrane will lead to direct contact between the substances in the two polar regions, exchange of solutions, and difficulty in separation and purification.

[0005] The performance of the diaphragm is extremely critical to the efficiency and safety of the system. Under high voltage, high current and strong acid and alkali solutions, damage to the diaphragm will lead to a decrease in its selective permeability. In severe cases, it may cause direct contact between hydrogen and oxygen, increasing the risk of explosion of the device. In the prior art, the unit price of the diaphragm is expensive and the service life is short, making the cost of the electrolysis device difficult to control. The equipment also needs to be frequently disassembled and inspected, limiting its large-scale application. Summary of the invention

[0006] The present invention provides a method for electrochemical synthesis reaction using an inorganic solid electrolyte as a diaphragm, the method comprising a method for preparing an inorganic solid electrolyte, and a method for electrochemical synthesis reaction using an inorganic solid electrolyte as a diaphragm. The method of the present invention is applicable to high voltage, high current, organic solution, normal temperature and pressure conditions, and has the advantages of high Faraday efficiency, good mass transfer performance, flexible and simple operation, high yield and wide application range.

[0007] The present invention adopts the following technical scheme.

[0008] The invention discloses an inorganic solid electrolyte diaphragm for electrochemical synthesis reaction.

[0009] The invention discloses a method for preparing the inorganic solid electrolyte membrane, including a sol-gel method, a gel injection molding method, an electrostatic spinning method, a spray drying method, a hot pressing method, a cold pressing method, a casting method, a chemical vapor deposition method or a physical vapor deposition method.

[0010] The invention discloses a method for electrochemical synthesis reaction using an inorganic solid electrolyte as a diaphragm, wherein the inorganic solid electrolyte diaphragm is used to isolate a cathode chamber and an anode chamber.

[0011] In the present invention, in the electrochemical synthesis reaction, the cathode chamber and the anode chamber respectively undergo a reduction reaction and an oxidation reaction. Preferably, the electrochemical synthesis reaction includes hydrogen production reaction, ammonia synthesis reaction, and organic synthesis reactions such as oxidation reaction, hydrogenation reaction, halogenation reaction, amination reaction, coupling reaction, etc.

[0012] In the present invention, the inorganic solid electrolyte is one or more of a garnet-type electrolyte, a fluorite-type oxide electrolyte, a perovskite-structured oxide electrolyte, and a LAMOX-based electrolyte.

[0013] The present invention discloses a device for electrochemical synthesis reaction using the above inorganic solid electrolyte as a diaphragm, comprising an electrolytic cell and the above inorganic solid electrolyte diaphragm. The diaphragm divides the electrolytic cell into an independent anode chamber and cathode chamber, which can be used for oxidation and reduction reactions respectively.

[0014] The invention discloses a membrane electrode assembly for electrochemical synthesis reaction, comprising an inorganic solid electrolyte diaphragm and electrodes on both sides outside the inorganic solid electrolyte diaphragm. Furthermore, a catalyst layer may or may not be provided on the outside of the electrode.

[0015] The present invention discloses the application of the above-mentioned inorganic solid electrolyte diaphragm, device or membrane electrode assembly for electrochemical synthesis reaction in electrochemical synthesis reaction; wherein, the electrochemical synthesis reaction includes organic synthesis reaction, water electrolysis reaction, ammonia synthesis reaction; preferably, the organic synthesis reaction includes oxidation reaction, hydrogenation reaction, halogenation reaction, amination reaction or coupling reaction.

[0016] Preferably, electrodes and catalyst coatings can be prepared on both sides of the inorganic solid electrolyte membrane, that is, a membrane electrode assembly. For example, the anode side and the cathode side of the inorganic solid electrolyte membrane are coated with electrode materials and catalyst materials.

[0017] The present invention discloses a method for electrochemical synthesis reaction using the above-mentioned inorganic solid electrolyte diaphragm as a diaphragm, comprising the following steps: assembling an electrolytic cell and a membrane electrode assembly, connecting a DC power supply, and collecting products after the raw materials undergo electrochemical synthesis reaction. Specifically, assembling an electrolytic cell and a membrane electrode assembly, connecting a DC power supply, and collecting products through a collection bottle after the raw materials undergo electrochemical synthesis reaction.

[0018] Preferably, the membrane electrode assembly is prepared based on an inorganic solid electrolyte membrane; for example, the anode side and the cathode side of the inorganic solid electrolyte membrane are coated with electrode materials and catalyst materials, and the surface of the electrode or catalyst is flat and smooth.

[0019] In the present invention, the preparation method of the inorganic solid electrolyte membrane specifically includes: sol-gel method, gel casting method, electrostatic spinning method, spray drying method, hot pressing method, cold pressing method, casting method, chemical vapor deposition method, and physical vapor deposition method.

[0020] In the present invention, the sol-gel method comprises the following steps: aging a sol containing a metal alkoxide, an acidic catalyst and a solvent to obtain a gel, and then drying, pre-calcining and sintering to obtain an inorganic solid electrolyte membrane.

[0021] In a specific embodiment of the present invention, the sol-gel method for preparing an inorganic solid electrolyte membrane includes: selecting one or more metal alkoxides as precursors and dissolving them in an alcohol solvent to form a uniform solution; then adding an acidic catalyst to the solution to promote the hydrolysis reaction of the metal alkoxide to form a primary sol; then aging the primary sol at ambient temperature to promote the transformation of the sol to a gel; then drying the formed wet gel to remove the residual solvent therein; then pre-firing the dried gel to remove organic residues, and finally sintering the pre-firing gel to form an oxide ceramic membrane.

[0022] Preferably, the metal alkoxide includes one or more of tetrabutyl titanate, tetraisopropyl titanate, tetraethyl silicate, tetramethyl silicate, trimethyl aluminate, triethyl aluminate, tetrapropyl zirconate, and tetraethyl niobate, and its concentration in the solution is 0.1 to 1 M, where the concentration of the metal alkoxide is the sum of the concentrations of all metal alkoxides.

[0023] Preferably, the alcohol solvent is a C1-C4 alcohol reagent, such as ethanol and isopropanol.

[0024] Preferably, the acidic catalyst comprises one or more of HF / Al2O3, BF3 / Al2O3, CdS, and ZnS, and the pH value is 1.0-4.0; the molar ratio of the acidic catalyst to the metal alkoxide is 0.1-5, where the molar weight of the metal alkoxide is the sum of the molar weights of all metal alkoxides.

[0025] Preferably, the temperature of the hydrolysis reaction is 50-100° C. and the time is 1-12 h.

[0026] Preferably, the drying temperature is 40-100° C. and the drying time is 1-12 h.

[0027] Preferably, the pre-firing temperature is 300-800° C. and the time is 1-4 h.

[0028] Preferably, the sintering temperature is 800-1400° C. and the sintering time is 2-8 h.

[0029] In the present invention, the gel injection molding method comprises the following steps: injecting a sol containing a metal alkoxide, a stabilizer, a thickener and a solvent into a mold, standing and aging to form a gel; and then drying, pre-burning and sintering to obtain an inorganic solid electrolyte membrane.

[0030] In a specific embodiment of the present invention, the preparation of inorganic solid electrolyte membrane by gel casting method includes: selecting one or more metal alkoxides as precursors and dissolving them in an alcohol solvent, and adding a stabilizer to prevent aggregation and sedimentation of sol particles, then adding a thickener to the sol and mixing it evenly by stirring, and then injecting it into a mold, standing to form a wet gel, and then curing to form a dry gel, followed by aging treatment to improve the structural stability of the gel; then vacuum drying to remove the solvent and moisture in the dry gel, and then pre-firing the dried gel and finally sintering it to form an oxide ceramic membrane.

[0031] Preferably, the metal alkoxide includes one or more of tetrabutyl titanate, tetraisopropyl titanate, tetraethyl silicate, tetramethyl silicate, trimethyl aluminate, triethyl aluminate, tetrapropyl zirconate, and tetraethyl niobate, and its concentration in the alcohol solvent is 0.1 to 1 M, where the concentration of the metal alkoxide is the sum of the concentrations of all metal alkoxides.

[0032] Preferably, the alcohol solvent is a C1-C4 alcohol reagent, such as ethanol and isopropanol.

[0033] Preferably, the stabilizer is a surfactant, such as one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, ammonium dodecyl sulfate, and dodecyltrimethylammonium bromide, and the molar ratio of the stabilizer to the metal alkoxide is 0.1 to 5, where the molar amount of the metal alkoxide is the sum of the molar amounts of all metal alkoxides.

[0034] Preferably, the thickener is one or more of polyvinyl alcohol and carboxymethyl cellulose, and the molar ratio of the thickener to the metal alkoxide is 0.01-1, where the molar amount of the metal alkoxide is the sum of the molar amounts of all metal alkoxides.

[0035] Preferably, the curing time is 2 to 12 hours.

[0036] Preferably, the aging treatment is performed at a temperature of 40 to 60° C., a humidity of 60 to 90%, and a time of 1 to 12 h.

[0037] Preferably, the vacuum drying is carried out at a temperature of 60 to 80° C. and for a time of 1 to 12 h.

[0038] Preferably, the pre-firing temperature is 300-800° C. and the time is 1-4 h.

[0039] Preferably, the sintering temperature is 800-1400° C. and the sintering time is 2-8 h.

[0040] In the present invention, the electrospinning method includes the following steps: using a mixture containing an inorganic precursor, a polymer and a solvent as a spinning solution, electrospinning is performed to obtain a nanofiber membrane; the nanofiber membrane is placed at room temperature to remove residual solvent, and then pre-calcined and finally sintered to form an inorganic solid electrolyte membrane.

[0041] In a specific embodiment of the present invention, the electrospinning method for preparing an inorganic solid electrolyte membrane includes: selecting an inorganic precursor, a polymer and a solvent to mix to form a uniform solution suitable for electrospinning, then loading it into a syringe with a metal needle and connecting it to a high-voltage power supply with adjustable voltage, grounding the receiver and maintaining an appropriate distance from the syringe needle; then applying voltage to form a stable Taylor cone at the needle, the solvent evaporates as the jet flies toward the receiver, the polymer gradually solidifies to form fibers, and is randomly deposited on the receiver to form a nanofiber membrane with a certain thickness; the collected nanofiber membrane is then placed at room temperature to remove residual solvent, followed by pre-sintering and finally sintering to form an oxide ceramic membrane.

[0042] Preferably, the inorganic precursor includes one or more of titanium tetrachloride, cesium lead chloride, and cesium lead bromide, and the concentration of the inorganic precursor in the solution is 8 to 12 wt %. Here, the concentration of the inorganic precursor is the sum of the concentrations of all inorganic precursors.

[0043] Preferably, the polymer includes one or more of polyacrylonitrile, polylactic acid, and polycaprolactone, and the concentration of the polymer in the solution is 8 to 12 wt %. Here, the concentration of the polymer is the sum of the concentrations of all polymers.

[0044] Preferably, the solvent is one or more of dimethylformamide and dimethyl sulfoxide.

[0045] Preferably, the metal needle has a diameter of 0.5 to 0.7 mm.

[0046] Preferably, the appropriate distance between the receiver and the syringe needle is 10 to 30 cm.

[0047] Preferably, the applied voltage is 10-50 kV.

[0048] Preferably, the time of standing at room temperature is 12 to 48 hours.

[0049] Preferably, the pre-firing temperature is 300-800° C. and the time is 1-4 h.

[0050] Preferably, the sintering temperature is 800-1400° C. and the sintering time is 2-8 h.

[0051] In the present invention, the spray drying method comprises the following steps: spray drying a solution containing an inorganic precursor and a solvent to obtain a powder, and then pressing the powder into a film, pre-burning and finally sintering to form an inorganic solid electrolyte membrane.

[0052] In a specific embodiment of the present invention, the preparation of an inorganic solid electrolyte membrane by a spray drying method includes: selecting an inorganic precursor to be dissolved in a solvent to form a uniform solution, then loading it into the feeding system of a spray dryer, setting the temperature and pressure parameters required for drying, and atomizing the solution into fine droplets through a nozzle with the assistance of a high-pressure pump or airflow. The solvent evaporates rapidly when passing through a drying tower, and the generated powder is collected by a cyclone separator, and the consistency of the powder particle size is ensured by screening. The powder is pressed into a thin film, pre-fired, and finally sintered to form an oxide ceramic film.

[0053] Preferably, the inorganic precursor includes one or more of carbon metatungstate and lithium dimanganese tetraoxide, and the concentration of the inorganic precursor in the solution is 0.1-1 M. Here, the concentration of the inorganic precursor is the sum of the concentrations of all inorganic precursors.

[0054] Preferably, the solvent is one or more of deionized water, ethanol and isopropanol.

[0055] Preferably, during the spray drying process, the temperature of the hot air is controlled at 200-400° C., and the atomization pressure is controlled at 1-10 bar.

[0056] Preferably, the powder particles collected by the cyclone separator have a particle size of 1 to 10 μm.

[0057] Preferably, the pre-firing temperature is 300-800° C. and the time is 1-4 h.

[0058] Preferably, the sintering temperature is 800-1400° C. and the sintering time is 2-8 h.

[0059] In the present invention, the hot pressing method comprises the following steps: hot pressing the powder raw material to form an inorganic solid electrolyte membrane.

[0060] In a specific embodiment of the present invention, the hot pressing method for preparing an inorganic solid electrolyte membrane comprises: loading powder raw materials into a mold and filling it evenly; then placing the mold filled with powder into a hot pressing device, and setting the required hot pressing temperature, pressure and holding time.

[0061] Preferably, the powder raw material includes one or more of lithium zirconium oxide, lithium aluminum titanium phosphate, lithium germanium phosphorus sulfur, and lithium tantalum oxide.

[0062] Preferably, the hot pressing temperature is 1000-1500° C., the pressure is 10-50 MPa, and the holding time is 1-4 h.

[0063] In the present invention, the cold pressing method comprises the following steps: cold pressing the powder raw material, and then pre-sintering and sintering to form an inorganic solid electrolyte membrane.

[0064] In a specific embodiment of the present invention, the cold pressing method for preparing an inorganic solid electrolyte membrane includes: loading the powder raw material into a mold and filling it evenly, then fixing the mold filled with powder on a cold press, setting the required pressing pressure, and then pre-sintering the resulting film and finally sintering it to form an oxide ceramic film.

[0065] Preferably, the powder raw material includes one or more of lithium zirconium oxide, yttrium-stabilized zirconium oxide, lithium aluminum titanium phosphate, lithium germanium phosphorus sulfur, and lithium tantalum oxide.

[0066] Preferably, the cold pressing pressure is 10 to 50 MPa, and the holding time is 0 to 2 h.

[0067] Preferably, the pre-firing temperature is 300-800° C. and the time is 1-4 h.

[0068] Preferably, the sintering temperature is 800-1400° C. and the sintering time is 2-8 h.

[0069] In the present invention, the tape casting method comprises the following steps: tape casting a slurry containing powder raw materials, a binder and a solvent into a film, and then drying, pre-calcining and sintering to form an inorganic solid electrolyte membrane.

[0070] In a specific embodiment of the present invention, the preparation of an inorganic solid electrolyte membrane by a casting method includes: selecting a powder raw material, mixing it with a solvent and a binder to form a slurry, pouring the slurry into the hopper of a casting machine, adjusting the distance between the scraper and the base belt, setting the temperature and wind speed of the drying oven, and the slurry flows through the scraper under the action of gravity or pressure, and is evenly spread on the base belt to form a thin film; then drying the formed film to remove the residual solvent therein, and then pre-firing the dried film to remove organic residues, and finally sintering the pre-firing gel to form an oxide ceramic film.

[0071] Preferably, the powder raw material includes one or more of lithium zirconium oxide, yttrium-stabilized zirconium oxide, and lithium tantalum oxide.

[0072] Preferably, the solvent includes water and an organic solvent, such as methyl ethyl ketone, toluene, xylene, ethanol, trichloroethylene, and the like.

[0073] Preferably, the binder includes polyvinyl alcohol (PVA), cellulose (MC), polyacrylic acid (PAA) and the like.

[0074] Preferably, in the slurry, the concentration of the powder raw materials is 40-80 wt %, where the concentration of the powder raw materials is the sum of the concentrations of all the powder raw materials.

[0075] Preferably, the distance between the scraper and the base belt is adjustable to control the thickness of the film.

[0076] Preferably, the drying temperature is 40-150° C., the wind speed is conventional, and the drying time is 1-12 h.

[0077] Preferably, the pre-firing temperature is 300-800° C. and the time is 1-4 h.

[0078] Preferably, the sintering temperature is 800-1400° C. and the sintering time is 2-8 h.

[0079] In the present invention, the chemical vapor deposition method includes the following steps: depositing a precursor gas and a reaction gas on the surface of a substrate, and chemically reacting to form an inorganic solid electrolyte membrane.

[0080] In a specific embodiment of the present invention, the preparation of an inorganic solid electrolyte membrane by chemical vapor deposition includes: selecting a substrate material for cleaning and decontamination treatment, selecting a precursor gas and a reaction gas; heating a reaction chamber to a specific temperature, and precisely controlling the flow rate of the reaction gas to adjust the growth rate and composition of the film; the precursor gas and the reaction gas chemically react on the surface of the substrate to generate a solid substance and deposit it to form a thin film, and controlling the pressure in the reaction chamber to optimize the film quality; and controlling the growth time according to the desired film thickness.

[0081] Preferably, the substrate comprises a silicon wafer, a metal sheet or other inert materials.

[0082] Preferably, the precursor gas includes trimethylaluminum, zirconium tetrachloride, tetraethoxysilane, etc.

[0083] Preferably, the reaction gas includes water vapor, oxygen and the like.

[0084] Preferably, the temperature of the reaction chamber is 400-1200°C.

[0085] Preferably, the flow rate of the gas is 1 to 1000 sccm.

[0086] Preferably, the pressure in the reaction chamber is controlled at 0.1-10 atm.

[0087] In the present invention, the physical vapor deposition method comprises the following steps: depositing the target material on the surface of the substrate to form an inorganic solid electrolyte membrane.

[0088] In a specific embodiment of the present invention, the physical vapor deposition method for preparing an inorganic solid electrolyte membrane includes: selecting a substrate material for cleaning and decontamination treatment, selecting a target material, and using a turbomolecular pump and a dry pump combination to evacuate the vacuum; using a DC sputtering source, applying a DC bias to the target material, and introducing a working gas into the sputtering chamber; setting appropriate sputtering parameters and substrate temperature, and the sputtered atoms condense on the substrate surface to form a uniform oxide film, and finally performing annealing.

[0089] Preferably, the substrate material comprises a silicon wafer, a metal sheet or other inert materials.

[0090] Preferably, the target material includes aluminum oxide, silicon carbide, titanium nitride, etc.

[0091] Preferably, the vacuum environment of the reaction chamber is 10-6 Pa.

[0092] Preferably, the DC bias voltage is 200-800V.

[0093] Preferably, the working gas is argon, nitrogen, etc., and the gas flow rate is 10 to 50 sccm.

[0094] Preferably, the sputtering power is set to 1-20 W / cm 2 , the sputtering time is 1 to 6 h.

[0095] Preferably, the substrate temperature is set to 80-150°C.

[0096] Preferably, the pressure in the reaction chamber is controlled at 0.1-10 atm.

[0097] Preferably, the annealing treatment temperature is 600-1400° C., and the time is 2-8 h.

[0098] As a preferred technical solution, all the above preparation methods can select appropriate porogens when feeding according to the pore size and porosity required for the diaphragm, and finally remove them by ultrasonic cleaning after sintering.

[0099] Preferably, the pore-forming agent includes sodium carbonate, calcium carbonate, sodium chloride, starch, etc., and the mass ratio of the pore-forming agent to the inorganic material is 1: (2-20), where the mass of the inorganic material is the sum of the masses of all inorganic materials.

[0100] The present invention discloses for the first time a method for electrochemical synthesis reaction using an inorganic solid electrolyte as a diaphragm, including a method for preparing an inorganic solid electrolyte, and a method for electrochemical synthesis reaction using an inorganic solid electrolyte as a diaphragm. The solid electrolyte diaphragm has low cost, good chemical stability, long service life, and is generally suitable for electrochemical synthesis reactions. In the method, the positive and negative poles of the electrolytic cell are simultaneously utilized, and the device has high working efficiency. At the same time, different heterogeneous electrocatalysts can be easily replaced by coating, which expands the types of reactions applicable to the device of the invention. The synthesis scale can be increased by expanding the size of the electrolytic cell, and the operation is simple and suitable for industrial application. In particular, the present invention overcomes the technical prejudice of the prior art that inorganic solid electrolyte diaphragms are difficult to apply due to poor electrical conductivity at low temperatures, especially at room temperature. For the first time, an inorganic solid electrolyte is used as a diaphragm for electrochemical synthesis reactions, and unexpectedly achieves efficient electrochemical reactions including organic synthesis, electrolysis of water to produce hydrogen, and synthesis of ammonia. BRIEF DESCRIPTION OF THE DRAWINGS

[0101] Figure 1 This is a schematic diagram of the structure of an apparatus for performing electrochemical synthesis reactions using a solid electrolyte as a diaphragm, as provided in Example 1, wherein: 1-H-type electrolytic cell, 2-electrode / catalyst coating, 3-diaphragm, 4-DC power supply.

[0102] Figure 2 1 and 2 are SEM plan views of the solid electrolyte membrane in Example 1, wherein (a) is a SEM plan view and (b) is a SEM cross-sectional view.

[0103] Figure 3 A schematic diagram of the structure of an apparatus for electrochemical synthesis reaction using a solid electrolyte as a diaphragm provided in Example 7, wherein: 5-injection device, 6-electrolyzer, 7-membrane electrode assembly, 8-end plate, 9-anode / cathode chamber, 10-solid electrolyte diaphragm, 11-cathode electrode / catalyst coating, 12-anode electrode / catalyst coating, 13-peristaltic pump, 14-ear, 15-injection bottle, 16-collection bottle, 17-DC power supply.

[0104] Figure 4 These are SEM plan views of the solid electrolyte membrane in Example 7, wherein (a) is a SEM plan view and (b) is a SEM cross-sectional view.

[0105] Figure 5 The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction for 8 hours in Example 1, and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database, are the gas chromatography, mass spectrometry and standard mass spectrometry of the cathode mixed solution after reaction for 8 hours.

[0106] Figure 6The gas chromatography, mass spectrum and standard mass spectrum of the National Institute of Standards and Technology (NIST) database of the anode mixed solution after reaction for 8 hours in Example 2, and the gas chromatography, mass spectrum and standard mass spectrum of the NIST database of the cathode mixed solution after reaction.

[0107] Figure 7 The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction in Example 3 and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database after reaction of the cathode mixed solution are shown in FIG.

[0108] Figure 8 The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction in Example 4 and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database, and the cathode mixed solution after reaction.

[0109] Fig. 9 The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction in Example 5 and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database after reaction of the cathode mixed solution.

[0110] Fig.10 The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction in Example 6, and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database after reaction of the cathode mixed solution.

[0111] Fig.11 The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction in Example 7 and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database, and the cathode mixed solution after reaction.

[0112] Fig.12 The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction in Example 8 and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database, and the cathode mixed solution after reaction.

[0113] Fig.13 The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction in Example 9 and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database after reaction of the cathode mixed solution.

[0114] Fig.14The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction in Example 10 and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database, and the cathode mixed solution after reaction.

[0115] Fig.15 These are the gas chromatography, mass spectrometry and standard mass spectrometry of the National Institute of Standards and Technology (NIST) database of the anode mixed solution after reaction in Comparative Example 1, and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database of the cathode mixed solution after reaction. DETAILED DESCRIPTION

[0116] The present invention discloses a method for electrochemical synthesis reaction using an inorganic solid electrolyte as a diaphragm, the method comprising a method for preparing the inorganic solid electrolyte and a method for electrochemical synthesis reaction using the inorganic solid electrolyte as a diaphragm, wherein the method for preparing the inorganic solid electrolyte specifically comprises: sol-gel method, gel injection molding method, electrostatic spinning method, spray drying method, hot pressing method, cold pressing method, casting method, chemical vapor deposition method, and physical vapor deposition method.

[0117] In the present invention, the inorganic solid electrolyte membrane is a layered structure or a uniformly distributed structure composed of one or more of a garnet-type electrolyte, a fluorite-type oxide electrolyte, a perovskite structure oxide electrolyte, and a LAMOX-based electrolyte. It has a multi-microporous structure, is resistant to strong acids and alkalis and a variety of organic solvents, can block the penetration of reaction molecules, and realize efficient and highly selective oxidation and reduction reactions in the anode chamber and the cathode chamber at the same time.

[0118] The method of the present invention for performing electrochemical synthesis reactions using an inorganic solid electrolyte as a diaphragm is based on an electrolytic cell, and realizes efficient and highly selective oxidation and reduction reactions in the anode chamber and the cathode chamber at the same time, and is generally applicable to important synthesis reactions such as electrolysis of water, electrochemical oxidation, hydrogenation, halogenation, amination, coupling, etc.

[0119] In the present invention, the solid electrolyte material needs to block the penetration of organic molecules while preventing the exchange of solutions between the anode and cathode. At the same time, the solid electrolyte material maintains a certain chemical stability in the solution required for the reaction and also maintains a certain mechanical toughness in the reaction container.

[0120] The present invention provides a device for electrochemical synthesis reaction using a solid electrolyte as a diaphragm, comprising an electrolytic cell and the above-mentioned inorganic solid electrolyte diaphragm. The diaphragm divides the electrolytic cell into independent anode chambers and cathode chambers, which can be used for oxidation and reduction reactions respectively; the diaphragm is an inorganic solid electrolyte diaphragm prepared according to the above method, such as a garnet-type electrolyte, a fluorite-type oxide electrolyte diaphragm, a perovskite structure oxide electrolyte diaphragm, and a LAMOX-based electrolyte diaphragm, and the size of the pores of the solid electrolyte also blocks the penetration of organic molecules.

[0121] Preferably, electrodes and catalyst coatings can be prepared on both sides of the inorganic solid electrolyte membrane, that is, a membrane electrode assembly. For example, the anode side and the cathode side of the inorganic solid electrolyte membrane are coated with electrode materials and catalyst materials.

[0122] The method disclosed in the present invention for electrochemical synthesis reaction using an inorganic solid electrolyte membrane as a membrane comprises the following steps: assembling an electrolytic cell and a membrane electrode assembly, connecting a DC power supply, and collecting products through a collecting bottle after the raw materials undergo electrochemical synthesis reaction.

[0123] Preferably, the membrane electrode assembly is prepared based on an inorganic solid electrolyte membrane; for example, the anode side and the cathode side of the inorganic solid electrolyte membrane are coated with electrode materials and catalyst materials, and the surface of the electrode or catalyst is flat and smooth.

[0124] Preferably, the electrolytic cell can be a flow-type electrolytic cell, and is connected to a sampling device and a collecting device, which can be communicated through a peristaltic pump device, specifically a conventional technology.

[0125] In the present invention, the pore size of the inorganic solid electrolyte membrane is 0.1-100 nm, and the thickness is 0.01-5 mm; preferably, the pore size of the inorganic solid electrolyte membrane is 1-50 nm, and the thickness is 1-5 mm; further preferably, the pore size of the inorganic solid electrolyte membrane is 1-20 nm, and the thickness is 1-2 mm. It should be noted that the present invention does not make specific requirements and special limitations on the shape and size of the inorganic solid electrolyte membrane. The role of the inorganic solid electrolyte membrane in the present invention is to divide the electrolytic cell into independent anode chambers and cathode chambers. Therefore, those skilled in the art can adaptively adjust the size of the solid electrolyte membrane according to the usage scenario and test conditions.

[0126] The technical progress of the present invention is illustrated below through specific experiments. The raw materials involved are conventional products that meet the conventional requirements of electrolytes. The specific experimental operations and test methods are conventional techniques; the test methods for product characterization, conversion rate, and selectivity are all conventional techniques. Unless otherwise specified, the operations are carried out in air. Example 1

[0127] This embodiment provides a paired electrochemical synthesis reaction, which is Figure 1 The device shown in the figure is completed, wherein 1 is an H-type electrolytic cell, 2 is an electrode, 3 is a diaphragm, and 4 is a DC power supply. The specific steps are as follows: The sol-gel method was used to prepare an inorganic solid electrolyte as a diaphragm. Specifically, 0.1 mol of trimethyl aluminate was used as a precursor and dissolved in 10 mL of isopropanol solvent to form a uniform solution. Then, 0.05 mol of CdS catalyst and 0.005 mol of starch pore former were added, and the mixture was stirred at 60°C for 4 h and then transferred to a conventional mold and allowed to stand to obtain a gel. The mixture was then placed in a vacuum drying oven and dried at 80°C for 8 h, and then transferred to a tubular furnace and heated from room temperature to 600°C at 5°C / min for pre-calcination for 2 h, and then heated to 1100°C at 1°C / min for sintering for 4 h to obtain a solid oxide diaphragm. The pore size of the inorganic solid electrolyte membrane prepared in this example is concentrated in the range of 2 to 11 nm, and the membrane thickness is about 1 mm; According to conventional methods, hydrophilic carbon paper is selected as the anode electrode and a Pt sheet is selected as the cathode electrode; during use, a catalyst may be coated on the electrode as required.

[0128] Toluene was added to a 1 M HBr and acetonitrile mixed solution to prepare a 200 mM anode reaction solution, and furfural was added to a 1 M HBr and acetonitrile mixed solution to prepare a 200 mM cathode reaction solution; and they were added to the corresponding tanks respectively; In CA mode, the voltage was set to 5 V. After 4 h of reaction, the gas chromatograph and gas chromatography-mass spectrometer were used to test and analyze that bromomethylbenzene was obtained at the anode with a conversion rate of 49% and a selectivity of 97%, and furfuryl alcohol was obtained at the cathode with a conversion rate of 53% and a selectivity of 99%. After 8 h of reaction, the gas chromatograph and gas chromatography-mass spectrometer were used to test and analyze that bromomethylbenzene was obtained at the anode with a conversion rate of 95% and a selectivity of 99%, and furfuryl alcohol was obtained at the cathode with a conversion rate of 99% and a selectivity of 99%.

[0129] Figure 2 (a) is a SEM plan view of the solid electrolyte membrane in this embodiment; Figure 2 (b) is a SEM cross-sectional view of the solid electrolyte membrane in this example. Example 2

[0130] This embodiment provides a paired electrochemical synthesis reaction, which is basically the same as that in Embodiment 1, except that: styrene is added to a mixed solution of 1 M HBr and acetonitrile to prepare a 200 mM anode reaction solution, and styrene is added to a mixed solution of 1 M HBr and acetonitrile to prepare a 200 mM cathode reaction solution; the voltage is set to 5.5 V in CA mode, and after 8 h of reaction, 2-bromoacetophenone is obtained at the anode with a conversion rate of 97% and a selectivity of 96% through gas chromatograph and gas chromatography-mass spectrometry. The conversion rate of ethylbenzene obtained at the cathode is 97% and the selectivity is 99%. Example 3

[0131] This embodiment provides a paired electrochemical synthesis reaction, which is basically the same as that in Example 1, except that the solid electrolyte membrane is prepared by electrospinning with titanium tetrachloride as a precursor, as follows: The electrospinning method was used, titanium tetrachloride was used as the precursor, and polyacrylonitrile was used as the polymer. Both were dissolved in dimethylformamide at a concentration of 10 wt%, and mixed and stirred to obtain the spinning solution. A 0.5 mm metal needle was selected, the receiver and the syringe needle were kept 20 cm, a voltage of 40 kV was applied, and the electrospinning instrument was started for deposition 3 times, each time for 20 min. After the deposition, the nanofiber membrane was collected and allowed to stand at room temperature for 20 h, transferred to a tubular furnace, heated from room temperature to 600 °C at 5 °C / min for pre-calcination for 2 h, and then heated to 1100 °C at 1 °C / min for sintering for 4 h to obtain a solid oxide diaphragm.

[0132] Toluene was added to a mixed solution of 1 M HBr and acetonitrile to prepare a 200 mM anode reaction solution, and furfural was added to a mixed solution of 1 M HBr and acetonitrile to prepare a 200 mM cathode reaction solution, which were added to the corresponding tanks respectively; the voltage was set to 5 V in CA mode, and after 8 h of reaction, the results were tested and analyzed by gas chromatograph and gas chromatography-mass spectrometry, and bromomethylbenzene was obtained at the anode with a conversion rate of 97% and a selectivity of 96%; furfuryl alcohol was obtained at the cathode with a conversion rate of 95% and a selectivity of 99%. Example 4

[0133] This embodiment provides a paired electrochemical synthesis reaction, which is basically the same as that in Embodiment 3, except that benzyl alcohol is added to a mixed solution of ammonia and acetonitrile to prepare a 200 mM anode reaction solution, and benzaldehyde is added to a mixed solution of 1 M KOH and acetonitrile to prepare a 200 mM cathode reaction solution; the voltage is set to 6 V in CA mode, and after 24 h of reaction, benzonitrile is obtained at the anode with a conversion rate of 98% and a selectivity of 86% through gas chromatograph and gas chromatography-mass spectrometry test and analysis; benzyl alcohol is obtained at the cathode with a conversion rate of 91% and a selectivity of 97%. Example 5

[0134] This embodiment provides a paired electrochemical synthesis reaction, which is basically the same as that in Example 1, except that: the solid electrolyte membrane is prepared by hot pressing method using lithium lanthanum zirconium oxide as a precursor, specifically as follows: hot pressing method is selected, lithium lanthanum zirconium oxide is used as a precursor, 1 g of powder sample is weighed, mixed with 0.05 g of starch pore-forming agent, and loaded into a cylindrical tablet mold after conventional ball milling, and uniform filling of powder is achieved by vibration; then the mold filled with powder is placed in a hot pressing device, and the pressure is maintained at 1300°C and 40MPa for 4 hours to obtain a solid oxide membrane.

[0135] Toluene was added to a 1 M HBr and acetonitrile mixed solution to prepare a 200 mM anode reaction solution, and furfural was added to a 1 M HBr and acetonitrile mixed solution to prepare a 200 mM cathode reaction solution; and they were added to the corresponding tanks respectively; In CA mode, the voltage was set to 5 V. After 8 h of reaction, the results of gas chromatography and gas chromatography-mass spectrometry showed that bromomethylbenzene was obtained at the anode with a conversion rate of 98% and a selectivity of 97%, and furfuryl alcohol was obtained at the cathode with a conversion rate of 96% and a selectivity of 99%. Example 6

[0136] This embodiment provides a paired electrochemical synthesis reaction, which is basically the same as that in Embodiment 5, except that: benzyl bromide and butyl bromide are added to a 1 M KOH tetrahydrofuran mixed solution to prepare a 200 mM anode reaction solution, and styrene is added to a 1 M HBr and acetonitrile mixed solution to prepare a cathode reaction solution; the voltage is set to 5.5 V in CA mode, and after 8 h of reaction, pentylbenzene is obtained at the anode with a conversion rate of 99% and a selectivity of 86% through gas chromatograph and gas chromatography-mass spectrometry testing and analysis; ethylbenzene is obtained at the cathode with a conversion rate of 96% and a selectivity of 95%. Example 7

[0137] This embodiment provides a paired electrochemical synthesis reaction, which is Figure 3 The device shown is completed, wherein 1 is a sample injection device, 2 is an electrolytic cell, 3 is a membrane electrode assembly, 4 is an end plate, 5 is an anode / cathode chamber, 6 is a solid electrolyte diaphragm, 7 is a cathode electrode, 8 is an anode electrode, 9 is a peristaltic pump, 10 is a pole ear, 11 is a sample injection bottle, 12 is a collection bottle, and 13 is a DC power supply. The specific steps are as follows: The cold pressing method was selected, with 5% yttrium-stabilized zirconia as the precursor, 1 g of powder sample was weighed, mixed with 0.05 g of starch pore-forming agent, and loaded into a square tablet mold after conventional ball milling. Uniform filling of the powder was achieved by vibration; then the mold containing the powder was placed in a cold pressing device, the required pressure was set to 40 MPa, and the holding time was 2 h. The resulting film was then transferred to a tubular furnace, heated from room temperature to 600 °C at 5 °C / min, pre-sintered for 2 h, and then heated to 1300 °C at 1 °C / min and sintered for 4 h to obtain a solid oxide diaphragm.

[0138] A platinum target with a mass fraction of 80% was selected and directly sputtered on the cathode side of a solid electrolyte YSZ diaphragm made by cold pressing with yttrium-stabilized zirconia by magnetron sputtering for 30 minutes to obtain a nano-scale thin film electrode; the cut carbon paper was attached to the anode side of the solid electrolyte diaphragm to obtain a membrane electrode assembly; When in use, a catalyst can also be coated on the electrode as needed.

[0139] An electrolyzer chamber with a cathode and an anode chamber of 2 cm×2 cm×1 cm was selected, and the prepared membrane electrode assembly was fixed between the chambers to assemble an electrolyzer; Add styrene to 1 M HBr solution to prepare a 200 mM anode reaction solution, and add furfural to 1 M HBr solution to prepare a cathode reaction solution; add them to the corresponding tanks respectively; In CA mode, the voltage is set to 4 V; The peristaltic pump was started and the flow rate was adjusted to 5 mL / min. The mixture after the electrochemical synthesis reaction continuously flowed into the collection bottle. After 6 h of reaction, the mixture was tested and analyzed by gas chromatograph and gas chromatography-mass spectrometry. 1-phenyl-2-bromoethanol was obtained at the anode with a conversion rate of 99% and a selectivity of 96%. Furfuryl alcohol was obtained at the cathode with a conversion rate of 99% and a selectivity of 82%.

[0140] Figure 4 (a) is a SEM plan view of the solid electrolyte membrane YSZ in this embodiment; Figure 4 (b) is a SEM cross-sectional image of the solid electrolyte membrane YSZ in this example. Example 8

[0141] The present embodiment provides a paired electrochemical synthesis reaction, which is basically the same as that in Example 7, except that: the solid electrolyte membrane is prepared by gel casting method using tetrabutyl titanate as a precursor: the gel casting method is selected, tetrabutyl titanate is used as a precursor and dissolved in an ethanol solution to form a 0.5 M tetrabutyl titanate-ethanol solution, and 0.1 M sodium dodecyl sulfate is added as a stabilizer and 0.05 M polyvinyl alcohol is added as a thickener, and then injected into a mold after stirring, and allowed to stand to form a wet gel, which is cured for 8 hours to form a dry gel, and then aged at a temperature of 60°C, a humidity of 80%, and a time of 8 hours, and then vacuum dried at 80°C for 12 hours, and then the obtained film is transferred to a tubular furnace and heated from room temperature to 600°C at 5°C / min for pre-sintering for 2 hours, and then heated to 1300°C at 1°C / min for sintering for 4 hours to obtain a solid oxide membrane.

[0142] Styrene was added to 1 M HBr solution to prepare a 200 mM anode reaction solution, and furfural was added to 1 M HBr solution to prepare a cathode reaction solution, which were added to the corresponding tanks respectively; the voltage was set to 4 V in CA mode. After 6 h of reaction, the results were tested and analyzed by gas chromatograph and gas chromatography-mass spectrometry. 1-phenyl-2-bromoethanol was obtained at the anode with a conversion rate of 99% and a selectivity of 97%; furfuryl alcohol was obtained at the cathode with a conversion rate of 96% and a selectivity of 98%. Example 9

[0143] This embodiment provides a paired electrochemical synthesis reaction, which is basically the same as that in Embodiment 7, except that: the solid electrolyte membrane is prepared by chemical vapor deposition using trimethylaluminum as a precursor: a silicon wafer is selected as a substrate material for cleaning and decontamination treatment, trimethylaluminum is selected as a precursor gas, and oxygen is selected as a reaction gas; the reaction chamber is heated to 1100° C., and the flow rate of 200 sccm of the reaction gas is precisely controlled to adjust the growth rate and composition of the film; the precursor gas and the reaction gas chemically react on the surface of the substrate to generate a solid substance and deposit to form a thin film, and the pressure in the reaction chamber is controlled to be 1 atm to optimize the film quality; the growth time is controlled according to the required film thickness.

[0144] Styrene was added to 1 M HBr solution to prepare a 200 mM anode reaction solution, and furfural was added to 1 M HBr solution to prepare a cathode reaction solution, which were added to the corresponding tanks respectively; the voltage was set to 4 V in CA mode. After 6 h of reaction, the results were tested and analyzed by gas chromatograph and gas chromatography-mass spectrometry. 1-phenyl-2-bromoethanol was obtained at the anode with a conversion rate of 96% and a selectivity of 97%; furfuryl alcohol was obtained at the cathode with a conversion rate of 97% and a selectivity of 96%. Example 10

[0145] This embodiment provides a paired electrochemical synthesis reaction, which is basically the same as that in Embodiment 7, except that: the solid electrolyte membrane is prepared by physical vapor deposition with aluminum oxide as a precursor: physical vapor deposition is selected, a corundum sintered plate is selected, the substrate material is subjected to conventional cleaning and decontamination treatment, aluminum oxide is used as a precursor target, and is placed in a magnetron sputtering coating machine, evacuated to 10 Pa, a DC sputtering source is used, a DC bias of 600 V is applied to the target, argon gas is introduced into the sputtering chamber, the gas flow rate is 30 sccm, and the sputtering parameters are set to 10 W / cm 2 The sputtering time was 6 h and the substrate temperature was 120 o C, the pressure in the reaction chamber was controlled at 1 atm, and then the obtained film was transferred to a tube furnace and heated from room temperature to 1400°C at 5°C / min and sintered for 4 h to obtain a solid oxide diaphragm.

[0146] Styrene was added to 1 M HBr solution to prepare a 200 mM anode reaction solution, and furfural was added to 1 M HBr solution to prepare a cathode reaction solution, which were added to the corresponding tanks respectively; the voltage was set to 4 V in CA mode. After 6 h of reaction, the results were tested and analyzed by gas chromatograph and gas chromatography-mass spectrometry. 1-phenyl-2-bromoethanol was obtained at the anode with a conversion rate of 98% and a selectivity of 97%; furfuryl alcohol was obtained at the cathode with a conversion rate of 97% and a selectivity of 99%. Embodiment 11

[0147] This embodiment provides an application of a diaphragm in a water electrolysis reaction, which is achieved by Figure 3 The device shown is completed. The specific steps are as follows: The cold pressing method was selected, and 5% yttrium-stabilized zirconia was used as the precursor and placed in a vacuum drying oven for constant temperature drying at 80°C for 12 h. After thorough grinding, 1 g of the powder sample was weighed, mixed with 0.05 g of starch pore-forming agent, and loaded into a square tablet mold after thorough ball milling. Uniform filling of the powder was achieved by vibration; then the mold containing the powder was placed in a cold pressing device, the required pressure was set to 40 MPa, and the pressure holding time was 2 h. Subsequently, the obtained film was transferred to a tubular furnace, heated from room temperature to 600°C at 5°C / min, pre-sintered for 2 h, and then heated to 1300°C at 1°C / min and sintered for 4 h to obtain a solid oxide diaphragm.

[0148] A platinum target with a mass fraction of 80% was selected and directly sputtered on the cathode side of a solid electrolyte YSZ diaphragm made by cold pressing with 5% yttrium-stabilized zirconia by magnetron sputtering. The sputtering time was 30 minutes to obtain a nano-scale thin film electrode. A nickel target with a mass fraction of 80% was selected and directly sputtered on the anode side of a solid electrolyte YSZ diaphragm made by cold pressing with lithium lanthanum zirconium oxide by magnetron sputtering. The sputtering time was 30 minutes to obtain a nano-scale thin film electrode. An electrolyzer chamber with a cathode and an anode chamber of 2 cm×2 cm×1 cm was selected, and the prepared membrane electrode assembly was fixed between the chambers to assemble an electrolyzer; 3 M KOH was prepared as the reaction solution for the anode and cathode and added to the corresponding tanks respectively; the current was set to 40 mA in CC mode; the peristaltic pump was started and the flow rate was adjusted to 2 mL / min; by replenishing the solution, the device could observe the continuous and stable generation of bubbles at the anode and cathode, achieving continuous water electrolysis operation for more than 500 h. Example 12

[0149] The present embodiment provides a paired electrochemical synthesis reaction, which is basically the same as that in Example 11, except that: the solid electrolyte membrane is prepared by a tape casting method using lithium lanthanum zirconium oxide as a precursor: the tape casting method is selected, lithium zirconium oxide is used as a precursor, and is placed in a vacuum drying oven at 80°C for constant temperature drying for 12 h. After sufficient grinding, the powder sample is weighed, mixed with 1 wt% starch pore-forming agent, and xylene is added as a solvent, PVA is used as a binder, and a slurry with a powder raw material concentration of 75 wt% is mixed. The slurry is poured into the hopper of the tape casting machine, the distance between the scraper and the base belt is adjusted to 1 mm, the temperature of the drying oven is set to 150°C, the time is 4 h, and a film is obtained. The obtained film is then transferred to a tubular furnace and heated from room temperature to 600°C at 5°C / min for pre-sintering for 2 h, and then heated to 1300°C at 1°C / min for sintering for 4 h to obtain a solid oxide membrane.

[0150] 3 M KOH was prepared as the reaction solution for the anode and cathode and added to the corresponding tanks respectively; the current was set to 40 mA in CC mode; the peristaltic pump was started and the flow rate was adjusted to 2 mL / min; by replenishing the solution, the device could observe the continuous and stable generation of bubbles at the anode and cathode, achieving continuous water electrolysis operation for more than 500 h.

[0151] Comparative Example 1 This comparative example provides a device for electrochemical synthesis reaction using Nafion117 membrane as a diaphragm. The difference from Example 1 is that the diaphragm 3 is replaced by Nafion117 membrane, and the other parameters and experimental conditions are the same as those in Example 1. After 4 hours of reaction, the anode obtained bromomethylbenzene with a conversion rate of 43% and a selectivity of 95% through gas chromatograph and gas chromatography-mass spectrometry test and analysis; the cathode obtained furfuryl alcohol with a conversion rate of 47% and a selectivity of 99%. After 8 hours of reaction, the Nafion117 membrane lost its selective permeability through gas chromatograph and gas chromatography-mass spectrometry test and analysis, and the solution in the two polar regions was mixed with the substance. However, after the above reaction of the present invention for 8 hours or even longer, the selective permeability was not lost, and the solution in the two polar regions was not mixed with the substance.

[0152] Comparative Example 2 This comparative example provides a device for electrochemical synthesis reaction using an anion exchange membrane (Fumasep FAA-3-50) as a diaphragm, which is different from Example 1 in that the diaphragm 3 is replaced by an anion exchange membrane, and the other parameters and experimental conditions are the same as those of Example 1. After 1 h of reaction, the anion exchange membrane is dissolved, and the solution in the two polar regions is mixed with the substance.

[0153] Comparative Example 3 This comparative example provides a device for electrochemical synthesis reaction using a bipolar membrane (Fumasep FBM-PK) as a diaphragm, which is different from Example 1 in that the diaphragm 3 is replaced by a bipolar membrane, and the other parameters and experimental conditions are the same as those of Example 1. After 2 h of reaction, the bipolar membrane is dissolved, and the bipolar region solution is mixed with the substance.

[0154] Comparative Example 4 This comparison provides a LAGP (Li 1.5 Al 0.5 Ge 1.5 The device for electrochemical synthesis reaction using (PO4)3) electrolyte as a diaphragm is different from Example 1 in that the diaphragm 3 is replaced by LAGP electrolyte, and the other parameters and experimental conditions are the same as those of Example 1. After 1 h of reaction, the LAGP electrolyte is dissolved, and the solutions in the two polar regions are mixed with the substance.

[0155] The present invention conducts conventional characterization on the above experimental products, which is as follows: Figure 5The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction for 8 hours in Example 1, and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database, are the gas chromatography, mass spectrometry and standard mass spectrometry of the cathode mixed solution after reaction for 8 hours.

[0156] Figure 6 The gas chromatography, mass spectrum and standard mass spectrum of the National Institute of Standards and Technology (NIST) database of the anode mixed solution after reaction for 8 hours in Example 2, and the gas chromatography, mass spectrum and standard mass spectrum of the NIST database of the cathode mixed solution after reaction.

[0157] Figure 7 The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction in Example 3 and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database after reaction of the cathode mixed solution are shown in FIG.

[0158] Figure 8 The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction in Example 4 and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database, and the cathode mixed solution after reaction.

[0159] Fig. 9 The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction in Example 5 and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database after reaction of the cathode mixed solution.

[0160] Fig.10 The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction in Example 6, and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database after reaction of the cathode mixed solution.

[0161] Fig.11 The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction in Example 7 and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database, and the cathode mixed solution after reaction.

[0162] Fig.12 The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction in Example 8 and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database, and the cathode mixed solution after reaction.

[0163] Fig.13The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction in Example 9 and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database after reaction of the cathode mixed solution.

[0164] Fig.14 The gas chromatography, mass spectrometry and standard mass spectrometry of the anode mixed solution after reaction in Example 10 and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database, and the cathode mixed solution after reaction.

[0165] Fig.15 These are the gas chromatography, mass spectrometry and standard mass spectrometry of the National Institute of Standards and Technology (NIST) database of the anode mixed solution after reaction in Comparative Example 1, and the gas chromatography, mass spectrometry and standard mass spectrometry of the NIST database of the cathode mixed solution after reaction.

[0166] By comparison, the device of the present invention using a solid electrolyte as a diaphragm for electrochemical synthesis reaction has a similar reaction conversion rate and selectivity when applied to toluene halogenation and furfural hydrogenation reactions, and the solid electrolyte diaphragm has relatively stable physical and chemical properties, will not be corroded and damaged after the reaction, still has selective permeability and high efficiency, and the solutions and substances in the two polar regions are still isolated.

[0167] The electrochemical synthesis reactions carried out by the existing technology all use membranes that are selectively permeable to ions. However, the performance of tolerating organic solvents and solutions containing some special ions (such as halogen ions) is poor. Therefore, the industrial application of water electrolysis and electrochemical organic reactions urgently needs to find alternatives to electrolyte membranes. Inorganic solid electrolyte membranes have higher chemical and thermal stability, can remain stable in a wider range of pH values ​​and chemical environments, and have higher performance under normal temperature liquid phase reaction conditions. They effectively isolate the two polar regions to adapt to various types of reactions, extend the service life of the electrochemical system, and reduce operating costs. In summary, the research on methods for electrochemical synthesis reactions using inorganic solid electrolytes as membranes is of great value, which helps to achieve more efficient, safer and more economical electrolysis processes, meets the requirements of green chemistry and sustainable development, and promotes the development of clean energy technologies.

[0168] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for electrochemical synthesis reaction using an inorganic solid electrolyte as a diaphragm, characterized in that: The cathode chamber and the anode chamber are separated by the inorganic solid electrolyte membrane; the inorganic solid electrolyte is one or more of a garnet-type electrolyte, a fluorite-type oxide electrolyte, a perovskite structure oxide electrolyte, and a LAMOX-based electrolyte; in the electrochemical synthesis reaction, a reduction reaction and an oxidation reaction occur in the cathode chamber and the anode chamber, respectively.

2. The method for electrochemical synthesis reaction using an inorganic solid electrolyte as a diaphragm according to claim 1, characterized in that: The preparation methods of inorganic solid electrolytes include sol-gel method, gel casting method, electrospinning method, spray drying method, hot pressing method, cold pressing method, casting method, chemical vapor deposition method or physical vapor deposition method.

3. The method for electrochemical synthesis reaction using an inorganic solid electrolyte as a diaphragm according to claim 1, characterized in that: The electrochemical synthesis reaction includes one or more of hydrogen production reaction, ammonia synthesis reaction, and organic synthesis reaction.

4. The method for electrochemical synthesis reaction using an inorganic solid electrolyte as a diaphragm according to claim 1, characterized in that: The solvent of the electrochemical synthesis reaction includes one or more of an inorganic solvent and an organic solvent.

5. A device for electrochemical synthesis reaction using an inorganic solid electrolyte membrane, characterized in that: It comprises an electrolytic cell and the inorganic solid electrolyte diaphragm; the inorganic solid electrolyte is one or more of a garnet-type electrolyte, a fluorite-type oxide electrolyte, a perovskite structure oxide electrolyte, and a LAMOX-based electrolyte; in the electrochemical synthesis reaction, a reduction reaction and an oxidation reaction occur in the cathode chamber and the anode chamber respectively.

6. A membrane electrode assembly for electrochemical synthesis reaction, characterized in that: It includes an inorganic solid electrolyte membrane and electrodes on both sides outside the inorganic solid electrolyte membrane; the inorganic solid electrolyte is one or more of a garnet-type electrolyte, a fluorite-type oxide electrolyte, a perovskite structure oxide electrolyte, and a LAMOX-based electrolyte; in the electrochemical synthesis reaction, a reduction reaction and an oxidation reaction occur in the cathode chamber and the anode chamber respectively.

7. The membrane electrode assembly for electrochemical synthesis reaction according to claim 6, characterized in that: The outside of the electrode may or may not be provided with a catalyst layer.

8. Use of an inorganic solid electrolyte membrane, a device for electrochemical synthesis reaction using an inorganic solid electrolyte membrane as claimed in claim 5, or a membrane electrode assembly for electrochemical synthesis reaction as claimed in claim 6 in an electrochemical synthesis reaction, characterized in that: The inorganic solid electrolyte is one or more of a garnet-type electrolyte, a fluorite-type oxide electrolyte, a perovskite-structured oxide electrolyte, and a LAMOX-based electrolyte; in the electrochemical synthesis reaction, a reduction reaction and an oxidation reaction occur in the cathode chamber and the anode chamber, respectively.

9. The use according to claim 8, characterized in that: Electrochemical synthesis reactions include organic synthesis reactions, water electrolysis reactions, and ammonia synthesis reactions.

10. A method for electrochemical synthesis reaction using an inorganic solid electrolyte membrane as a membrane, characterized in that: The following steps are involved: Assemble an electrolytic cell with the inorganic solid electrolyte membrane as a diaphragm, connect a power supply, collect the product after the raw materials undergo electrochemical synthesis reaction; the inorganic solid electrolyte is one or more of a garnet-type electrolyte, a fluorite-type oxide electrolyte, a perovskite structure oxide electrolyte, and a LAMOX-based electrolyte.

Citation Information

Patent Citations

  • Method for optimising the conductivity provided by the displacement of h+ protons and / or oh- ions in a conductive membrane

    CN101689670A

  • Decarboxylation cell for production of coupled radical products

    CN102471903A

  • Electrochemical synthesis of aryl-alkyl surfactant precursor

    CN102782191A

  • Electrolysis system and electrolysis method for the same

    CN103781731A

  • Channeled articles and methods for their manufacture

    CN105188893A